COVID-19 and social vulnerability in the state of Sergipe, Brazil: an ecological study (Research, Society and Development, 2022)
COVID-19 was characterized by the WHO as a pandemic on March 11, 2020. In Sergipe, northeastern Brazil, the first case was diagnosed on March 14, 2020. This study is part of analyzes on the first year of the pandemic of COVID-19 in Sergipe and aims to analyze, through an ecological study, deaths from the disease in its 75 municipalities, statistically correlating the crude and age-standardized mortality rates with indicators of social vulnerability and human development used in the country; and with the demographic density of the municipalities in the state. Mortality data were obtained by dividing the absolute number of deaths by the number of inhabitants in each municipality. Direct standardization of mortality rates and Spearman correlation ( ρ ) were performed to test the described correlation. The study demonstrated a different correlation from that found in the literature between the Municipal Human Development Index and deaths by COVID-19: the greater the development, the more deaths by COVID-19 were identified. The effects of these indicators may be being offset by factors such as the greater demographic density of the cities with greater development, which could favor the transmission of the disease.